Phytolacca exiensis, a new species of Phytolaccaceae from west of Hubei province, China - Xie, Dan; Qian, Dan; Zhang, Meng-Hua; Wang, Ye-Qing; Wu, Yu; Huang, Lu-Qi; Zhang, Dai-Gui (Phytotaxa, 2017)
Phytolacca exiensis, a new species of Phytolacca which was discovered from west of Hubei province, China, is discribed and illustrated in this paper. The placement of this new species is accessed based on molecular phylogenetic analysis of the nuclear ribosomal ITS and one chloroplast regions (psbA-trnH) sequences together with mophorlogical comparison. This new species can be easily distinguished from other related species by its carpers connate and plants dioecious.